P117 Does the differential measurement error of pulse oximeters in patients with non-white skin delay the initiation of oxygen therapy?. (11th November 2022) - Williams, M; Holt, R; Churchill, J; Singh, R; Shaw, D; Fogarty, A
Abstract : Introduction and Objectives: Recent studies have demonstrated differences that the measurement error of oxygen saturation as measured by pulse oximetry is higher in patients with non-white skin; the error giving higher oxygen saturations than the true value. We hypothesised that this may lead to patients with non-white skin being referred for long-term oxygen therapy (LTOT) later than those with white skin if pulse oximetry is used to inform the timing of this decision. Method: We used data collected routinely from patients referred for LTOT assessment from 2013 to the present day. Their oxygen saturation, pH, pO2, pCO2, bicarbonate and carboxyhaemoglobin were tabulated and compared and stratified by ethnic group. The analysis was registered as an Audit. Results: Data were available from 516 patients referred for LTOT assessment. There were significant differences in oxygen levels measured by arterial blood gas between ethnic groups (ANOVA, p<0, 0001) with the lowest mean measurements in those with black skin (4.76kPa, N=3). There was also a negative association between carboxyhaemoglobin COHb and oxygen levels -0.23 kPa (95% confidence intervals CI -0.35 to -0.11) and female sex and oxygen levels -0.40 (95% CI: -0.66 to -0.14) in a multivariate regression model that also included age. Conclusion: People with black skin had lower oxygen levels at the point of referral for LTOT. The reasons for this are unclear but may reflect the known inaccuracy of pulse oximetry in darker skin. Female sex and carboxyhaemoglobin levels were associated with lower pO2 at LTOT, suggesting that gender and exposure to tobacco smoke may be associated with later referrals.